Isolation and identification of pathogenic bacteria isolated from aceh cattle liver infected by Fasciola gigantica based on microbiological and biochemical assay - Sari, S.Si, M.Si, Wahyu Eka; Zamzami, Rumi Sahara; Hambal, Muhammad; Ferasyi, Teuku Reza; Qomariah, Annisa Nurul; Riandi, Lian Varis; Muttaqien, Muttaqien; Zulkifli, Baidillah (The International Journal of Tropical Veterinary and Biomedical Research, 2024)
Fasciolosis is a disease caused by fluke infestation Fasciola gigantica and Fasciola hepatica. Usually, these flukes infect ruminants such as cattle, goats, sheep and wildlife. Infestation F. gigantica can cause a decrease in the immune response, so that livestock become more susceptible to infection with other microorganisms. The emergence of microorganisms such as bacteria can cause foodborne disease for those who consume liver infestation by F. gigantica. This study aims to see the presence of pathogenic bacteria in the liver of cattle infestation by F. gigantica. Isolation of bacteria present in beef liver was conducted by culturing it on culture media such as blood agar media. Blood agar media can be used to determine pathogenic bacteria. Pathogenic properties of bacteria are seen based on the ability of bacteria to hemolyze blood on blood agar media. Based on the results of the hemolysis test on blood agar media, four colonies were found that were potentially pathogenic, namely alpha hemolysis (isolate S2-A) and beta hemolysis (isolate S1.1-A, S2-B, and S3-A). Furthermore, the results of bacterial identification were based on morphological observations and Gram staining tests as well as biochemical tests and spore staining, isolate S2-A identified as bacteria Staphylococcus sp., while isolates S1.1-A, S2-B, and S3-A were identified as bacteria Bacillus sp. Thus, it can be concluded that in the liver of cattle infestation by F. gigantica, bacteria are found that have the potential to be opportunistic pathogens.